2008
DOI: 10.3113/fai.2008.0950
|View full text |Cite
|
Sign up to set email alerts
|

Late-Stage Freiberg Disease Treated by Osteochondral Plug Transplantation: A Case Series

Abstract: Osteochondral plug transplantation for late-stage Freiberg disease yielded satisfactory results upon arthroscopic and radiological evaluations at 12 months after surgery and clinical evaluation for all four cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 13 publications
1
45
1
1
Order By: Relevance
“…To date, there have been few reports that revealed the effectiveness of OAT for Freiberg disease [10][11][12]. In 2002, Hayashi et al first reported a case of late stage Freiberg disease that was treated by OAT with a good surgical outcome [10].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…To date, there have been few reports that revealed the effectiveness of OAT for Freiberg disease [10][11][12]. In 2002, Hayashi et al first reported a case of late stage Freiberg disease that was treated by OAT with a good surgical outcome [10].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, although favourable results have been reported [10][11][12], evidence remains insufficient to support its application. To date, there had been no reports on the surgical outcome and midterm follow-up of this technique in at least ten cases.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Surgical treatment is typically only performed when conservative therapy fails. Although various operative procedures, including resection arthroplasty, joint debridement, osteotomy, and osteochondral transplant, have been reported, no consensus regarding the best surgical approach has been reached to date [2][3][4][5][6][7][8][9][10][11][12]. Gauthier and Elbaz reported good results for dorsal intra-articular closingwedge osteotomy procedures regardless of the disease stage [4].…”
Section: Introductionmentioning
confidence: 99%